A case report of a rare case of uterine fibroid herniating as recurrent incisional hernia (Indian Journal of Case Reports, 2020)
Uterine leiomyoma is the most common estrogen-dependent benign tumor of the uterus. Approximately 5–20% occur in the reproductive age group. It is composed of smooth muscle and fibrous tissue. Asymptomatic myomas present in 50% of cases. The incisional hernia develops in the scar of a surgical incision. We are presenting a case of fibroid uterus with recurrent incisional hernia in a 51-year-old, morbidly obese female patient with swelling over the midline of the abdomen for 3 years. The patient was a second para patient with a history of one cesarean delivery 24 years ago followed by one normal delivery 18 years ago. The patient has a history of incisional hernia meshplasty 12 years ago. She was subjected to ultrasound and magnetic resonance imaging abdomen with pelvis which confirmed fibroid uterus herniating as a recurrent incisional hernia. Management of the case is discussed.